2012
DOI: 10.1152/physiolgenomics.00148.2011
|View full text |Cite
|
Sign up to set email alerts
|

Identification of hypertrophy- and heart failure-associated genes by combining in vitro and in vivo models

Abstract: Heart failure (HF) is a complex disease involving multiple changes including cardiomyocyte hypertrophy (growth). Here we performed a set of screens in different HF and hypertrophy models to identify differentially expressed genes associated with HF and/or hypertrophy. Hypertensive Ren2 rats and animals with postmyocardial infarction (post-MI) HF were used as in vivo HF models, and neonatal rat cardiomyocytes treated with hypertrophy inducing hormones phenylephrine, endothelin-1, and isoproterenol were used as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 31 publications
1
32
1
Order By: Relevance
“…In a previous gene array study, we identified AKIP1 as a differentially expressed gene in cardiac hypertrophy [19]. By RT-PCR and by using a custom made AKIP1 specific antibody we first analyzed changes in AKIP1 expression both at the mRNA and protein level in hypertrophied and remodeled heart tissue.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a previous gene array study, we identified AKIP1 as a differentially expressed gene in cardiac hypertrophy [19]. By RT-PCR and by using a custom made AKIP1 specific antibody we first analyzed changes in AKIP1 expression both at the mRNA and protein level in hypertrophied and remodeled heart tissue.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, one of the identified genes that was prominently upregulated was AKIP1 [19]. In humans, there are three splice variants, the full-length protein (AKIP1a), one that lacks the third exon (AKIP1b), and one that lacks the third and fifth exon (AKIP1c).…”
Section: Introductionmentioning
confidence: 99%
“…Primary neonatal rat ventricular cardiomyocytes (NRVCs) were isolated from neonatal rats of 1-3 days old, as previously described (12,14). The use of animals for these studies was in accordance with the National Institutes of Health Guide for the Care and Use of Laboratory Animals.…”
Section: Methodsmentioning
confidence: 99%
“…This finding raises the possibility that either premature glucocorticoid exposure fails to mimic the normal maturational effects of glucocorticoids upon the heart, or that indirect dysmaturational effects predominate. Secretion of cardiac natriuretic peptide A (ANP; encoded by Nppa) is stimulated by stretch of the myocardium (27) and is considered a marker of cardiomyocyte hypertrophy (28). Its expression increases with gestation, as apparent in Hsd11b2 +/+ fetuses (1.8-fold between E14.5 and E17.5) (Fig.…”
Section: Gene Expression Patterns In Hsd11b2 −/− Fetal Hearts Reflectmentioning
confidence: 99%